BASELINE VALUES OF OXIDATIVE STRESS BIOMARKERS IN CATTLE (Indian Journal of Animal Production and Management, 2014)
The goal of this study is to summarize the baseline values of both enzymatic and non enzymatic oxidative stress biomarkers in cattle. Blood samples were collected from ten (10) crossbred cattle from Instructional Bovine Farm, Ranchi Veterinary College, BAU, Ranchi that were screened on the basis that the animals were clinically healthy. Different antioxidants biomarkers were estimated using standard methods. The superoxidase dismutase, glutathione peroxidase and glucose-6-phosphate dehydrogenase activities in hemolysate of healthy animals were 391.023±25.930 U/L, 123.556±5.208 U/ mg and 11.907±1.287 U/gm Hb respectively. The malonyl dialdehyde produced was 1.904±0.132 nmol/g Hb. The serum albumin and uric acid concentration were 4.325±0.222 gm/dl and 2.927 ± 0.159 mg/dl respectively. The concentration of total serum bilirubin, direct bilirubin (conjugated) and indirect bilirubin (non-conjugated) in the healthy animals in the study were 0.467 ± 0.055, 0.329 ± 0.015 and 0.138 ± 0.023 mg/dl respectively. This study will provide a database that will be useful in clinical Biochemistry.
Keywords: Baseline values; Oxidative stress biomarkers; Cattle